Leather Shoes Business Development Digital Based Marketing Strategy in West Bandung Regency (International Journal of Psychosocial Rehabilitation, 2020)
This study revealed that there is a gap (gap) between strategy-based programs and business development on IKM shoes in West Bandung Regency. This study aims to determine whether digital-based marketing strategies have an effect on determining the business development of shoe SMEs in West Bandung Regency. The factors tested in this study are digital marketing strategies as independent variables and business development as the dependent variable. The research method used is the descriptive method, with data collection techniques through observation and questionnaire distribution. The population in the study was the shoes of SMEs and entrepreneurs, with a research sample of 63 respondents. Data analysis using multiple linear regression analysis at a significant level of 5%. The program used is SPSS 25. The results of the study showed that the independent variable, digital-based marketing strategy, was influential in determining the business development of shoe SMEs in West Bandung Regency.